Cultivation of maggot from organic waste to increase economic value at TPS 3R Enggal Comfort, Gondosuli, Muntilan - Eko Muh Widodo; Muhamad Ardi Yuwono; Rohmat Haryadi; Ade Hirani Noverizka; Gunawan Sholeh Sholahudin; Ayu Ainayya (Community Empowerment, 2021)
Gondosuli Village is located in Muntilan District, Magelang Regency, and has a high population growth rate, economy, and development, all of which contribute to increased community activities. This causes waste production to continue to rise; additionally, there are issues with waste management from upstream to downstream, namely a lack of waste reduction, which leads to waste accumulation in landfills. This is due to a lack of proper management, which consists of only collection, disposal, and transportation. As a result, the community service is carried out by planning for a solid waste management system capable of reducing waste from upstream. The cultivation of maggots from organic waste is an upstream system approach that can be used to solve the waste problem. BSF maggot cultivation has several advantages, including the production of pre-puppa, which can be used as a source of protein for animal feed, and aiding in the resolution of the community's organic waste processing problem. The concept of integrated waste management (TPS 3R) can be combined with a waste bank to reduce waste disposal in the TPA while also providing economic value.